Targeted Poverty Alleviation in China: A Typology of Official–Household Relations. (July 2021) - Davie, Georgina; Wang, Mark; Rogers, Sarah; Li, Jie
'Targeted Poverty Alleviation' (TPA) is the Chinese government's latest anti-poverty policy, aiming to lift the remaining 70 million Chinese citizens above the poverty line by 2020. The TPA scheme is novel in that every impoverished household is paired one-on-one with a local government official, who then bears responsibility for the eradication of their poverty. Despite being at the core of TPA, this pairing mechanism has received little academic attention. Based on an empirical case study of ten households across two villages in rural Shaanxi Province, China, this article aims to investigate this pairing mechanism at the micro level and its outcomes for poverty alleviation, in order to better understand how the notion of 'precision' is being realized through TPA. Two distinct traits that influence the TPA pairing system emerged: first, the ranking of the assigned local official is important in that higher-ranked officials have greater social and financial resources at their disposal, bringing about enhanced poverty alleviation outcomes for their households compared with lower-ranked officials. Secondly, the willingness and ability of impoverished households to actively participate in their poverty alleviation programme is beneficial within the TPA scheme, achieving better outcomes in the long-term compared with households who are passive receivers. TPA has the potential to work effectively and to achieve China's poverty reduction goals; however, our analysis shows that some pairing mechanisms are more effective in achieving poverty alleviation goals than others.